Two new species of Endecous Saussure, 1878 (Orthoptera: Grylloidea: Phalangopsidae) from caves in central-western Brazil, with the proposition of a new subgenus to accommodate E. vitreus Bolfarini & Campos, 2023 - Carvalho, Pedro Henrique Mendes; Castro-Souza, Rodrigo Antônio; Ferreira, Rodrigo Lopes (Zootaxa, 2023)
The genus Endecous (Orthoptera, Grylloidea, Phalangopsidae) encompasses over 20 species, grouped into four subgenera: E. (Endecous), E. (Pedroecous), E. (Notendecous), and E. (Ramalhoecous). In this study, we present the description of two novel species belonging to the subgenus Endecous (Endecous) Saussure, 1878 (Phalangopsidae) discovered in caves located within the Serra da Bodoquena region of Mato Grosso do Sul state, Brazil. The descriptions are based on the distinguishing male genitalia characteristics, among other traits. Furthermore, we introduce a new subgenus, namely Endecous (Bodoquenaecous), specifically created to accommodate the recently discovered species E. vitreus, also found in caves within the same area. Initially, E. vitreus was placed under the subgenus Endecous; however, due to its numerous distinct traits, the establishment of a new subgenus became justified. In this study, we also introduce the first pictorial key for the subgenera within the genus Endecous. Additionally, we briefly discuss observed troglomorphic adaptations in species belonging to this genus. Finally, comprehensive ecological observations and conservation status assessments are provided for both newly described species, as well as for E. vitreus.